ICTs to address information inefficiencies in food supply chains - Van Campenhout, Bjorn (Wiley, 2022)
In developing countries, incomplete and/or asymmetric information contributes to inefficiencies in food supply chains. Various products and services have emerged that rely on Information and Communication Technologies (ICTs) to facilitate information flows between agro-input providers, farmers, traders, and consumers. However, not all initiatives are equally effective and many struggle to reach scale. In this article, I review some of the earlier services that generally targeted farmers with price information to reduce search costs and increase their bargaining power vis-a-vis traders. I reflect on the reasons why these initiatives often led to disappointing results and provide examples of (complementary) interventions that look more promising. Furthermore, I highlight some of the dangers of relying too much on ICT-mediated information, such as exclusionary networks, bias in crowdsourced data, and “fake news.” Finally, I explore why ICT applications that address information inefficiencies seem to be less successful than innovations that address other barriers to efficient and inclusive food supply chain development, such as risk or credit constraints.